Public Sector Accountability and Performance: The Influence of Institutional Scale, Legislative Oversight, and Supreme Audit Judgements - Ria Dwi Putri; Raden Budi Hendaris (E-Jurnal Akuntansi, 2025)
Regional financial performance is commonly assessed through the independence ratio, which serves as an indicator of a region’s fiscal autonomy. Despite decentralisation reforms aimed at empowering local governments, the persistently low independence ratios observed across many regions suggest that the realisation of regional autonomy remains suboptimal. This study seeks to provide empirical evidence on the relationship between three institutional variables—local government size, legislative size, and audit opinion issued by the Audit Board of Indonesia (Badan Pemeriksa Keuangan, BPK)—and the financial performance of local governments. The analysis draws on secondary data collected from official sources, namely the Central Bureau of Statistics (www.jabar.bps.go.id) and the Audit Board of Indonesia (www.jabar.bpk.go.id), covering the 2019–2023 period. The study adopts a census approach, encompassing all 27 local governments (18 districts and 9 cities) within West Java Province. A multiple linear regression analysis was conducted using IBM SPSS version 27 to test the proposed relationships. The findings reveal that local government size has a statistically significant positive association with financial performance, suggesting that larger jurisdictions may benefit from economies of scale or greater administrative capacity. Conversely, legislative size is found to have a significant negative effect, potentially indicating inefficiencies or coordination challenges in larger assemblies. The audit opinion issued by the BPK, however, does not appear to exert a statistically significant influence on financial performance, pointing to possible limitations in the extent to which external audit outcomes drive internal financial reforms. Keywords: Size of Local Government; Legislative Size; BPK Audit Opinion; Local Government Financial Performance